Investigation of corrosion and wear performance of TiNbTaZr/Cr-Mo PVD coatings on 316L SS in Hanks's solution for improved biomedical applications - Atmaca, I.; Dikici, B.; Ezirmik, K. V.; Bulutsuz, A. Gunay; Niinomi, M. (ELSEVIER SCIENCE SA, 2023)
316L stainless steel is popular due to its strength, durability, and especially cost-effectiveness in biomedical implant applications. However, the primary drawback of those materials is damage by corrosion and wear over prolonged exposure to the body's physiological environment. Thus, surface modification or coatings are essential to mitigate the corrosion and wear sensitivity of 316L implant materials. In this study, the corrosion and wear performance of TiNbTaZr/Cr-Mo PVD coatings on 316L stainless steel (SS) for improved biomedical applications have been investigated comprehensively. The coatings were deposited using an RF magnetron sputtering PVD system, and their morphological, structural, and wettability properties were characterized through SEM-EDS, GIXRD, and contact angle measurements. The coatings' hardness was compared by using the Knoop hardness method and their surface roughness was analyzed by using a profilometer. Electrochemical corrosion tests and wear studies were conducted in both dry and simulated body fluid (SBF) conditions. The results indicated that the coatings exhibited nano-sized grain structures with no instances of delamination or cracking and consisted of a stable 8-phase. The hardness of the coatings was significantly higher than that of the uncoated 316L sample. Contact angle measurements showed improved hydrophilicity for both coatings compared to uncoated 316L SS. Furthermore, the TNTZ-Mo coating demonstrated superior corrosion resistance and reduced wear under SBF conditions, making it a promising material for biomedical applications.
Keywords: PVD; Biomaterials; Corrosion; Wear; TiNbTaZr; Mo; Cr; PLASMA ELECTROLYTIC OXIDATION; MECHANICAL-PROPERTIES; TITANIUM-ALLOY; TI-29NB-13TA-4.6ZR ALLOYS; ELECTROCHEMICAL-BEHAVIOR; STAINLESS-STEEL; YOUNGS MODULUS; RESISTANCE; ADHESION; STABILITY; Materials Science; Physics